Sol-Gel Optics Processing and Applications - Klein, Lisa C. (The Springer International Series in Engineering and Computer Science, Electronic Materials: Science and Technology, 1994)
Sol--Gel--Optics encompasses numerous schemes for fabricating optical materials from gels -- materials such as bulk optics, optical waveguides, doped oxides for laser and nonlinear optics, gradient refractive index (GRIN) optics, chemical sensors, environmental sensors, and 'smart' windows. Sol--Gel--Optics: Processing and Applications provides in-depth coverage of the synthesis and fabrication of these materials and discusses the optics related to microporous, amorphous, crystalline and composite materials. The reader will also find in this book detailed descriptions of new developments in silica optics, bulk optics, waveguides and thin films. Various applications to sensor and device technology are highlighted. For researchers and students looking for novel optical materials, processing methods or device ideas, Sol--Gel--Optics: Processing and Applications surveys a wide array of promising new avenues for further investigation and for innovative applications. (This book is the first in a new subseries entitled 'Electronic Materials: Science and Technology)